Functional service quality satisfaction of islamic and conventional credit card users in Malaysia - N.R.S.M., Dali (Penerbit Universiti Kebangsaan Malaysia, 2015)
The objective of this paper is to deepen the understanding of customers' satisfaction among credit card users. The study employs the Servperf model to evaluate the functional service quality dimensions of satisfaction of credit card users of Islamic versus conventional banking in Malaysia. The comparison between different types of credit card users is examined using factor analysis and regression. The dimensions are found to be robust for different types of credit card users, except for the Assurance dimension. The dimension did not form significantly in the factor analysis whenever respondents, who are Islamic credit card users, are included. Meanwhile, all of the dimensions are found in the regression analysis to have positive relationships with customer satisfaction, which are consistent with the theoretical prediction. This is the first contextual study conducted in the credit card industry that compares the functional service quality satisfaction of Islamic credit card users with conventional credit card users.